Clinical Signs and Haematology Profiles of Beagle Dogs with Tick Infestation - Mihardi, Arief Purwo; Joesoef, Jayusman Arsiyanti; Wolo, Kathirina Beathrik Riwu; Esfandiari, Anita; Widhyari, Sus Derthi; Wulansari, Retno; Wijaya, Agus; Maylina, Leni (Universitas Airlangga, 2022)
Rhipicephalus sanguineus is one of the vectors that could induce diseases in dogs. A physical examination and haematology test could examine the dog's condition with tick infestation. Five dogs, beagle breeds from Veterinary Teaching Hospital, School of Veterinary Medicine and Biosciences, IPB University, have been examined for physical examination and CBC test. A haematology test was performed using a haematology analyzer and made the blood smear. Physical examination showed that 60% of dogs have a tick infestation, 80% have pallor, 60% have pruritus, 40% have crusted skin, and 100% have wounds in extremities. However, the body temperature and heart rate were relatively normal. Complete blood count test showed that red blood cells (RBC), peak cells volume, and haemoglobin (Hb) decreased (80%), MCHC increased (40%), thrombocytopenia (100%), leukopenia (40%), lymphocytopenia (60%), neutropenia (10%) and monositopenia (80%). The blood smear result showed all dogs have positive blood parasites, with the highest percentage being the third dog (0.056%). From the physical examination, CBC, and blood smear, it can be concluded that dogs with tick infestation would experience anaemia that showed by RBC, PCV, decreasing number of platelet and positive blood parasite.